2018
DOI: 10.1002/jbm.b.34205
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/β‐TCP nerve guidance conduits promote facial nerve regeneration in mini‐swine and the underlying biological mechanism: A pilot in vivo study

Abstract: This study aimed to evaluate the efficiency of new nerve guidance conduits (NGCs) in bridging facial nerve gaps, and investigate the underlying biological mechanisms implicated in the regeneration process. A collagen/β-TCP conduit was prepared and applied to a facial nerve gap in a mini-swine model. Functional recovery and axonal regeneration were further evaluated by electrophysiological and histological examinations at 3 months after surgery. Furthermore, the global transcriptomic profiles of regenerated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For a new bioengineering technology to be developed to meet clinical needs, preclinical studies are necessary. The animal models for preclinical studies of facial nerve injury repair include rodents, rabbits, and miniature pigs [36,37], among which rodents and rabbits are widely used because of their relatively low operation difficulty. The facial nerve distribution of these experimental animals is similar to that of humans.…”
Section: Development and Prospect Of Tissue Engineering Nerve Conduitmentioning
confidence: 99%
See 1 more Smart Citation
“…For a new bioengineering technology to be developed to meet clinical needs, preclinical studies are necessary. The animal models for preclinical studies of facial nerve injury repair include rodents, rabbits, and miniature pigs [36,37], among which rodents and rabbits are widely used because of their relatively low operation difficulty. The facial nerve distribution of these experimental animals is similar to that of humans.…”
Section: Development and Prospect Of Tissue Engineering Nerve Conduitmentioning
confidence: 99%
“…During the development process of facial nerve conduits, more preclinical studies were conducted in the experimental animal model of sciatic nerve injury, and there was still a dearth of research on the repair of facial nerve injury [36,126]. The complexity of the facial nerve's anatomical structure, along with its limited exposure and small operating space, poses challenges in terms of establishing the defect model.…”
Section: Prospectsmentioning
confidence: 99%
“…In addition, the studies demonstrated that the collagen in biomaterials would significantly stimulate the adhesion and proliferation of neural stem cells. [61][62][63] Imitating the composition of neural tissue to construct the biomaterials containing the pluripotent stem cellderived cells and collagen may be a future direction to regenerate neural tissue.…”
Section: Mimicking Tissue Composition For Skin and Neural Tissues Repairmentioning
confidence: 99%
“…Furthermore, the facial mimetic muscles of beagles are small and thin, making it difficult to perform electromyographical tests. Previous studies have indicated that minipigs and monkeys may be appropriate animal models for preclinical research regarding peripheral nerve injury and repair, although these models are associated with substantial costs and ethical circumspection (Satoda, 1987;Hontanilla et al, 2006;Lu et al, 2015;Aycart et al, 2015;Zhang et al, 2019;Milner et al, 2020). The buccal division of the facial nerve in minipigs is sufficiently thick, straight, and long that it can be used to bridge the defect of a single branch of the facial nerve.…”
Section: Introductionmentioning
confidence: 99%